Psychosocial Adjustment of Breast Cancer Patients Post-Treatment Therapy and Mentoring. (Case Study of 4 Breast Cancer Patients in Sapkandara Community Medan) - Melicha Athalia Pelawi; Erni Asneli Asbi (Global Academy of Multidisciplinary Studies, 2025)
Purpose: To determine the impact of therapy, psychosocial adjustments, and assistance received by breast cancer patients in the Sapkandara Movement community in Medan. Research Methodology: This type of research is qualitative with a case study approach to 4 breast cancer patients who are members of the Sapkandara Results: The results showed that patients with breast cancer experienced significant physical and psychological changes after therapy, including fatigue, hair loss, stress, and emotional instability. Socially, patients tend to withdraw from their environment. Psychosocial adjustment is influenced by patients' knowledge of the disease and family support. There are three types of assistance: existential, functional, and professional; however, only existential support from the family is effective. The Sapkandara Community provides comprehensive support, including information, hospital assistance, and moral and emotional support. Conclusions: Holistic support is crucial for patients with breast cancer, integrating family, social workers, and health professionals. The Sapkandara community plays a vital role in empowering patients and supporting psychosocial adjustment. Limitations: This study was limited the scope of research to patients with breast cancer who were undergoing treatment, support therapy, and were members of the Sapkandara. Contribution: This study contributes to social welfare knowledge by emphasizing the role of community-based support and social work in health settings. This study provides practical insights for policymakers, health institutions, and NGOs to strengthen psychosocial services for cancer patients.